SPATIAL DISTRIBUTION OF MANGROVE ECOSYSTEM IN CONSERVATION AREA OF TELUK KELUMPANG NATURE RESERVE - Asyari, Mufidah; Udiansyah, Udiansyah (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
Mangrove forest area of 98,494.6 ha (72.86%) is distributed in Kotabaru Regency. Based on the forest status, the mangrove forest consists of a nature reserve zone covering an area of 66,487.5 ha (67.50%), production forests 3,510.4 ha (3.57%), and area for other uses 28,496.7 ha (28.93%) (BKSDA, 2008 the Ministry of Forestry, 2009; Sirang et al., 2010). The purpose of this study was to find out the spatial distribution of mangrove ecosystem in Teluk Kelumpang Nature Reserve. The study was conducted using a remote sensing technology (Landsat 7 ETM + 2012 (Path/Row: 117/063) to obtain data of the extent, and the distribution of mangrove forest species in Teluk Kelumpang nature reserve. The measurement of mangrove vegetation was to find out the potency and characteristics of mangrove forest stands. The results showed that the potential vegetation in the area of Teluk Kelumpang nature reserve was R. apiculata, R. mucronata and B. gymnorhiza. Teluk Kelumpang nature reserve is divided into two zones. The first zone is proximal zone (50 m - 100 m from coastline), a zone dominated by R. apiculata and R. mucronata plants. The second is middle zone, a mixed zone comprising B. gymnorhiza, X. granatum, C. decandra, and N. fruticans, with the area of > 100 m - 500 m from the river line and coastline.